Políticas de financiamento para a educação superior: avaliação institucional e gestão orçamentária na Universidade Federal de Uberlândia/UFU (1995-2008) - Paiva, Silvani Aparecida Ribeiro de (2009)
This study connects to the line of research on Public Policy and Management Education, the Program for Master of Education / PPGED Federal University of Uberlândia / UFU. Aims for general comprehension of conceptions, principles, objectives, methodologies and uses of results of institutional assessment, in their different ways and its implications for financing, in budget management and in the performance of the institutions, through evaluation reports, analysis and distribution of budget resources available by the federal government for UFU, during the period 1995 to 2008. As specific objectives, whose organization guides the chapters 1 to 3, the following purposes: 1) identify the several aspects of public policy for Brazilian higher education on post-LDB period (Law 9394/96), focusing on the management prospects and assessment in Higher Education, considering even the current trends of the Program of Support to the restructuring plans and expansion of federal universities/REUNI; 2) examine the linkage between processes and results of institutional assessment with the budget management and financing of IFES, the government for higher education in a real education reform for the sector with reference to the principles, programs and procedures up from 1995; 3) locate and verify the relationship between evaluation, financing and budget management at the Federal University of Uberlândia, from 1995 to 2008, by the analysis of budget reports and spreadsheets of the institution, focusing on the implications for the institutional performance of UFU. Such objectives sought answer basic questions namely: which are the trends of policies of institutional assessment in the current context of reform of higher education? What relationships are established between the institutional assessment, financing and budget management of the Brazilian higher education? What are the concepts of assessment in the present proposals of the Ministry of Education? These issues are guiding element and indicators for our study on the assessment of higher education in the current scenario associated with academic and administrative management of UFU, the period from 1995 to 2008.